2021
DOI: 10.1186/s12889-021-11256-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential health impact of increasing adoption of sustainable dietary practices in Sweden

Abstract: Background An urgent transition to more sustainable diets is necessary for the improvement of human and planetary health. One way to achieve this is for sustainable practices to become mainstream. We estimated the potential health impact of wider adoption of dietary practices deemed by consumers, researchers and stakeholders in Sweden to be niche, sustainable and with the potential to be scaled up. Methods A life table method was used to estimate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This is similar to other research where the prevalence of obesity was reported to reduce by 1.5 to 10 percent when added sugar intake reduced by 10 to 20 percent [28,29]. Our results are also consistent with previous modelling studies showing improved health outcomes from diets that better align with dietary recommendations [30][31][32], and tally with the findings of previous modelling studies that have shown both health and economic gains resulting from a reduced intake of added sugars specifically [33][34][35]. Health and economic gains have also been reported as a result of the taxation of salt or foods high in salt in other countries [36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to other research where the prevalence of obesity was reported to reduce by 1.5 to 10 percent when added sugar intake reduced by 10 to 20 percent [28,29]. Our results are also consistent with previous modelling studies showing improved health outcomes from diets that better align with dietary recommendations [30][31][32], and tally with the findings of previous modelling studies that have shown both health and economic gains resulting from a reduced intake of added sugars specifically [33][34][35]. Health and economic gains have also been reported as a result of the taxation of salt or foods high in salt in other countries [36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…First, the top authors are Selena Ahmed and Rosemary Green with four articles each. Their recent works have contributed insights on food security (Ahmed et al, 2022), food waste (Ahmed et al, 2021), and sustainable dietary practices (Patterson et al, 2021) such as the EAT–Lancet dietary recommendations for health and sustainability (Ali et al, 2022), among others. Second, the top affiliations are Harvard T. H. Chan School of Public Health with 12 articles, London School of Hygiene and Tropical Medicine with eight articles, and John Hopkins Bloomberg School of Public Health with five articles.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed and Rosemary Green with four articles each. Their recent works have contributed insights on food security (Ahmed et al, 2022), food waste (Ahmed et al, 2021), and sustainable dietary practices (Patterson et al, 2021) such as the EAT-Lancet dietary recommendations for health and sustainability (Ali et al, 2022)…”
Section: Report Of the Rockefeller Foundation-lancet Commission On Pl...mentioning
confidence: 99%
“…3). Tere is an increasing concern for the environment due to growing consumption patterns, Patterson et al [83]; Ferrari et al [50]; Larrea-Gallegos and Vázquez-Rowe [49]; whereas Tompa et al [40] minimised the water footprint of the optimised diet. Springmann et al [84] highlighted that there is a tendency that the impact of consumers on the environment may worsen as the world population grows exponentially and dietary patterns continue to change.…”
Section: Deviation Minimisationmentioning
confidence: 99%